The teaching of Earth Sciences in basic and secondary education in Portugal - Bonito, Jorge (2017)
This work begins by framing the Portuguese Educational System. In a second moment, characterize the Earth Sciences Teaching throughout the non-higher education. Teaching Earth Sciences in basic and secondary education in Portugal has a long tradition. Currently, Earth Sciences are taught from the earliest years of elementary school through the end of upper secondary education. In the 1st cycle of basic education, the study of Earth Sciences is done in the discipline of Environmental Studies, although it is scarce enough during the four years that comprise this cycle of education. In the 2nd Cycle of Basic Education are taught contents of Earth Sciences in the discipline of Natural Sciences, namely in the 5th grade. The discipline of Natural Sciences, in the 7th grade, is entirely dedicated to Earth Sciences (since 2014-2015 there are curricular goals for this level). In secondary education, in the course of Science and Technology, students can choose, in the specific training, the subject of Biology and Geology (in the 10th and 11th grade) and, in the 12th grade, the Geology. Portugal participated for the first time in the 8th edition of the International Earth Science Olympiad, having since achieved bronze, silver and gold medals.